Integrated SiGe Detectors for Si Photonic Sensor Platforms - Grégory Pandraud; Silvana Milosavljevic; Amir Sammak; Matteo Cherchi; Aleksandar Jovic; Pasqualina Sarro (Proceedings, 2017)
In this work, we present the results of integrated Ge detectors grown on a Si photonic platform for sensing applications. The detectors are fabricated on a passive photonic circuit for maximum coupling efficiency. Measurement results at 1300 nm wavelength show a responsivity of 0.2 A/W and very low dark current levels. For a voltage range between 0 and −10 V, the dark current is better than 0.1 nA which is crucial for highly sensitivity devices and applications, like Optical Coherence Tomography.